The Effectiveness of Soil Improvement and Urea Fertilizer on Growth and Yield of Pagoda Mustard (Brassica narinosa L.) - sekar kinanti; Sunawan Sunawan; Indiyah Murwani (AGRONISMA, 2022)
Pagoda mustard (Brassica narinosa L.) is a plant with a crunchy leaf texture and the leaves are arranged like a blooming flower. Pagoda mustard requires N nutrients for leaf growth. Combined with soil improver to determine the effect of soil enhancer on pagoda mustard and reduce the use of chemical fertilizers, namely urea fertilizer. The design used is a factorial RAK which consists of two factors. The first factor in the application of soil improver is T0: without soil enhancer and T1: using soil improver. The second factor is the dose of urea fertilizer, namely U0: without urea fertilizer (0%), U1 (25% urea fertilizer), U2 (50% urea fertilizer), U3 (75% urea fertilizer) and U4 (100% urea fertilizer). From the results of the study, it was found that soil improver was able to reduce the dominant dose of urea fertilizer, the results were better in the treatment of T1U3 on plant height and total fresh weight of plants, T0U2 on number of leaves, and T1U4 on leaf area. As for the results of the Pagoda mustard, better results were obtained the T1U3 treatment.